Media interaktif berbasis kearifan lokal Kabupaten Jepara “Mesi” untuk menumbuhkan keterampilan menulis puisi pada siswa sekolah dasar - Rina Rochiana (COLLASE (Creative of Learning Students Elementary Education), 2023)
The purpose of this study was to analyze the design, feasibility, and effectiveness of learning media in the form of interactive media based on local wisdom of Jepara Regency to cultivate poetry writing skills in Indonesian language learning in class V Elementary School in Jepara Regency. The research method using research and development was adopted from Borg and Gall with three simplified stages, namely introduction, development, and effectiveness testing. Data collection techniques through observation, questionnaires and documentation. The effectiveness of teaching media was obtained from the pretest and posttest scores in the control class and the experimental class. Data analysis used descriptive analysis. This analysis was carried out during the validity test, the data was collected from the questionnaire assessment. The results showed that the interactive media based on the local wisdom of Jepara "Mesi" was declared feasible and could be used. This can be seen from the expert validation which states very well, as well as positive responses from teachers and students. The interactive media based on Jepara's local wisdom "Mesi" that has been developed is declared effective in improving students' poetry writing skills. This is evidenced by the test results of students' poetry writing skills in the experimental group which were better than the control class.